SYSTEMIC RELATIONS OF CRIMINAL LEGISLATION OF UKRAINE AS A REGULATORY PHENOMENON - Hrishchuk, Victor (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the analsis of systematic connections of сriminal legislation as a regulative phenomenon. The methodological basis of the study is comprised of scientific methods of cognitive science that author uses to solve the issue of relation of criminal legislation with other branches of national legislation. Results: the author emphasizes that criminal legislation of Ukraine as a regulative phenomenon of criminal law reality stays in сonstitutional and indissoluble connection with the norms of other branches of ukrainian legislation that specify its provision. Discussion: the author states that principles of criminal law regulation that are contatined in the norms of international law, resolutions of European Union on human rights, provisions of the Constitution of Ukraine and legal positions of Constitutional Court of Ukraine are embodied in criminal legislation. It has been stated that regulation of criminal law in its systematic sense should be of the highest quality. The criminal law mechanism for ensuring the quality of legal regulation in any sphere of social life is complex and multifacated. It covers, in particular, public and private institutes and organizations, legal framework of their activities and international cooperation. Each of these elements must be endowed with sufficient qualitative instrumental features. Additionally, it is important to ensure a harmonious systematic connection between them. With regard to criminal law, it can be argued about the quality of its form and content, bearing in mind the philosophical axiom that form is always essential, and the essence is always formed. It has been found that traditionally since the ancestor of the science of codification Jeremy Bentham, codes were considered the highest form of expression to improve the quality and content of legislation in the doctrine of law. They are precisely recognized as such in the continental legal system, as they most fully ensure, in particular, such qualities of the legislation as systematization, clarity, accessibility, the absence of gaps and contradictions. It has been investigated, that unfortunately, the Ukrainian legislative practice goes mainly through the creation of diverse, often contradictory and separate laws which make numerous changes to the current criminal law. Legal act is considered to be excellent when it does not require specification in by-laws, or if a need to specify the norms is minimal or enforced. The global law-marking practice has recognized that since ancient times such legal act is a code of laws, if it is developed and adopted on the scientific basis of codification techniques.